TAFSIR FENOMENOLOGI SIMBOLIK AL-QUR’AN - Ahmad Suhendra, Nunung Lasmana dan (STAIN Kediri, 2015)
the Qur’anic studies in Indonesia continue to experiencing a significant growth. Lukman Abdul Qohar Sumabrata, Lukman Saksono, and Anharudin offered a symbolic method of interpretation. They seek to interpret the Qur’an with different perspectives by looking at its format and structure, leading to different interpretations of the Qur’an. Lukman Abdul Qahar Sumabrata’s interpretation method attracted attentions from many people and encouraged them to study more closely the format and structure of the Qur’an. The interpretation of symbolic phenomenology refers to the format and structure of the Qur’an of the ‘Uthmāni script.Keywords: al-Qur’an, Fenomenologi Simbolik, Tafsir